Implementasi Metode Group Resume Dalam Meningkatkan Keaktifan Peserta Didik Pada Pembelajaran Pendidikan Agama Islam Kelas X Di Smk Batik 1 Surakarta - Yulianti, Dina; Ali, Muhammad (Instructional Development Journal, 2025)
This study aims to: Determine the application of the Group Resume method in increasing student activity and the positive and negative impacts of using the Group Resume method in Islamic Religious Education learning for grade 10 at SMK Batik 1 Surakarta. The researcher used qualitative research, which in this study is descriptive, for a case study at SMK Batik 1 Surakarta. The results show the use of the Group Resume method, a learning method carried out in groups of 5-6 students, then students' results are presented in front of the class to be listened to by other groups. The positive impact of using this method is that students understand the material because they search and explore the material, then work together and exchange opinions. The negative impact is that it requires a lot of time for students who should not exceed the allotted time and there are differences of opinion among students